A controlled clinical trial on the effects of motor intervention on balance and cognition in institutionalized elderly patients with dementia - Christofoletti, Gustavo; Oliani, Merlyn Mercia; Gobbi, Sebastiao [UNESP]; Stella, Florindo [UNESP]; Teresa, Lilian [UNESP]; Gobbi, Bucken [UNESP]; Canineu, Paulo Renato (Sage Publications Ltd, 2008)
Purpose: To analyse the effects of two interventions on the cognition and balance of institutionalized elderly people with mixed dementia.Methods: Fifty-four participants were allocated into three groups. Group 1 was assisted by an interdisciplinary programme comprising physiotherapy, occupational therapy and physical education. A physiotherapist alone carried out the intervention in group 2. Group 3 was considered as control. Assessors were blinded to guarantee the absence of bias. Cognitive functions were analysed with the Mini-Mental State Examination and the Brief Cognitive Screening Battery. Balance was assessed with the Berg Balance Scale and the Timed Get-Up-and-Go Test. Multiple analysis of variance (MANOVA) was used to test possible main effects of the interventions.Results: The results showed benefits on the balance of subjects in both groups 1 (F=3.9, P < 0.05) and 2 (F= 3.1, P < 0.05), compared with group 3. MANOVA did not indicate benefits on the cognitive functions between groups 1 and 3 (F= 1.1, P > 0.05) and groups 2 and 3 (F= 1.6, P > 0.05). However, univariate analysis indicated some benefits of the interdisciplinary intervention on two specific domains measured by the Brief Cognitive Screening Battery (F=26.5, P < 0.05; F= 4.4, P < 0.05).Conclusion: Six months of multidisciplinary or physiotherapeutic intervention were able to improve a person's balance. Although global cognition did not improve through treatment, when the intervention was carried out on a multidisciplinary basis we observed an attenuation in the decline of global cognition on two specific cognitive domains. Exercises applied in different contexts may have positive outcomes for people with dementia.